Investigation of the Effect of Doing Sports Frequency on Fear of Covid-19 - İlayda Şahin; Yunus Şimşek; Buğrahan Cesur; Adem Civan (Türk Spor ve Egzersiz Dergisi)
The aim of our research is to examine the fear levels of female and male athletes about the new type of corona virus (Covid-19). The survey method, one of the quantitative research models, was used in the study. The sample of the research consists of volunteers (n=139) who actively do sports in various sports clubs and in different branches in the districts of Istanbul, on the European side (Küçükçekmece, Bakırköy, Zeytinburnu). The data were collected online by applying the questionnaire technique. The COVID-19 Fear Scale of the athletes was used as a data collection tool. T-test and one-way ANOVA analyzes were used, which were determined to have a normal distribution of the data as a statistical procedure. It is seen that there is no difference between the levels of fear of Covid-19 according to the gender, age, education level, chronic disease level, training status, financial level of their families, sports branch, and years of playing sports. A significant difference was found between the levels of fear of Covid-19 according to the levels of how many days a week the athlete’s train. The change in the frequency of weekly training in covid-19 fear levels, for example, less fear in those who train 5 or more a week may be due to the decrease in their anxiety as they are more exposed to covid-19 as they go out. At the same time, people who keep their routine may be less afraid of the corona than those who are less socialized because they go out 5 days a week or more and maintain their routine and socialize at the same time, which can adversely affect their fear levels and cause them to be less afraid.